(untitled) - Maggs, David J. (St. Louis, Mo., 2013)
Recognize, diagnose, and manage a wide range of common ocular conditions with Slatter’s Fundamentals of Veterinary Ophthalmology, 5th Edition. Covering small and large animals including birds and exotic species, this reference provides the latest, most practical information on structure and function of the eye, ocular development, pathology, examination and diagnosis, surgical procedures, ophthalmic pharmacology and therapeutics, and management of ocular emergencies.
Keywords: Trung tâm Học liệu ĐHCT,Eye diseases; Bệnh mắt,Veterinary; Thú y